2009
DOI: 10.1523/jneurosci.2021-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Aβ Immunotherapy: Intracerebral Sequestration of Aβ by an Anti-Aβ Monoclonal Antibody 266 with High Affinity to Soluble Aβ

Abstract: Amyloid ␤ (A␤) immunotherapy is emerging as a promising disease-modifying therapy for Alzheimer's disease, although the precise mechanisms whereby anti-A␤ antibodies act against amyloid deposition and cognitive deficits remain elusive. To test the "peripheral sink" theory, whichpostulatesthattheeffectsofanti-A␤antibodiesinthesystemiccirculationaretopromotetheA␤effluxfrombraintoblood,westudiedthe clearance of 125 I-A␤ 1-40 microinjected into mouse brains after intraperitoneal administration of an anti-A␤ monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 27 publications
2
78
1
3
Order By: Relevance
“…Though it is possible that over longer periods of time (days to weeks), certain anti-Aβ antibodies may alter Aβ metabolism in the brain, this possibility was not assessed in these experiments. A recent study suggested that the anti-Aβ antibody, m266, alters Aβ metabolism in the CNS by entering the brain and sequestering soluble Aβ (49). The small fraction of antibody that entered the brain in our study did not alter Aβ levels in the ISF over a very short timeframe, perhaps a reflection of its lower affinity for Aβ compared with the m266 antibody.…”
Section: Discussioncontrasting
confidence: 46%
“…Though it is possible that over longer periods of time (days to weeks), certain anti-Aβ antibodies may alter Aβ metabolism in the brain, this possibility was not assessed in these experiments. A recent study suggested that the anti-Aβ antibody, m266, alters Aβ metabolism in the CNS by entering the brain and sequestering soluble Aβ (49). The small fraction of antibody that entered the brain in our study did not alter Aβ levels in the ISF over a very short timeframe, perhaps a reflection of its lower affinity for Aβ compared with the m266 antibody.…”
Section: Discussioncontrasting
confidence: 46%
“…This hypothesis stipulates that anti-Aβ antibodies cross the BBB and directly block the toxic effects of Aβ while mediating its clearance by promoting microglial engulfment or clearance as a complex via CSF/interstitial fluid (ISF) bulk flow. The latter may explain the peripheral rise in Aβ observed after dosing [28,63]. Consistent with this hypothesis, antibodies that fully engage microglia while binding plaque may cause reduction of amyloid plaque, but also disrupt the BBB causing vasogenic edema [62], a phenomenon renamed amyloid-related imaging abnormalities-edema [64].…”
Section: Using Anti-bace1 To Reduce Aβ Productionmentioning
confidence: 78%
“…Although there is evidence that peripherally originating or administered antibodies can act centrally [25][26][27][28], the mechanism(s) for such uptake is not entirely clear. Nevertheless, current evidence supports a steady-state equilibrium being established through a passive fluid phase mechanism relying on nonspecific uptake by endocytic vesicles in brain vasculature (Fig.…”
Section: Limited Quantities Of Therapeutic Antibodies Cross the Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamada et al [29] reported that monoclonal m266 with a high affinity for soluble Aβ may sequester soluble monomeric Aβ in the brain thereby preventing the formation of multimeric Aβ and related neurotoxicity. This concept was firstly reported by Solomon et al [22,23] who showed that a monoclonal anti-Aβ antibody prevent samyloid fibril formation.…”
Section: Intracerebral Sequestration Of Aβ In Monomeric Statementioning
confidence: 99%